A "living legacy" for nurses. Issue 9 (September 2021) - Graber, Jennifer; Saylor, Jennifer; Jackson, Amy; Hayes, Evelyn
Abstract : In this article, learn about the Building Your Nursing Legacy project designed to focus on legacy building in the nursing profession as nurses progress from students to experts.